Modelling of liquid metal flow and oxide film defects in filling of aluminium alloy castings - Dai, Xiaojun J.; Jolly, Mark R.; Yang, X.; Campbell, James C. (Cranfield University, 2012)
The liquid metal flow behaviours in different runner system designs have important effects on the mechanical strength of aluminium alloy castings. In this paper, a new model has been developed which is a two-dimensional program using a finite difference technique and the Marker and Cell (MAC) method to simulate the flow of liquid metal during filling a mould. In the program the Eulerian method has been used for the liquid metal flow, while the Oxide Film Entrainment Tracking Algorithm (OFET) method (a Lagrangian method) has been used to simulate the movement of the oxide film on the liquid metal surface or in the liquid metal flow. Several examples have been simulated and tested and the relevant results were obtained. These results were compared with measured bending strengths. It was found that the completed program was capable of simulating effectively the filling processes of different runner systems. The simulation results are consistent with the experiment. In addition, the program is capable of providing clearer images for predicting the distribution of the oxide film defects generated during filling a mould.